Exploring the factors of social media in facilitating knowledge-sharing among university academics: a case study approach - Aziz, Faiq (Inderscience, 2023)
Social media is becoming a vital medium for knowledge-sharing. Although many researchers have attempted to understand the role of social media on knowledge-sharing in organisations, their impact on higher education institutions and academics is still unclear. This study covers interviews with 32 Malaysian academics to determine the elements that influence knowledge-sharing on social media and to assist higher education institutions in leveraging these elements to improve their knowledge-sharing. Five themes and 10 sub-themes emerged from the interviews, including motivational factors (enjoyment in helping others, financial rewards and reciprocal benefits), a social factor (social interaction tie), a social barrier (knowledge hoarding), organisational factors (open communication climate, training and management support) and technological factors (functionality and ease of use). Moving forward, this research gives managers and policymakers valuable insights into how higher educational institutions' stakeholders might be encouraged to feel the need to share knowledge and how they can utilise social media to do so effectively.